The Influence of Personality, Communication and Work Stress Towards Employee Performance at PT. Gunungdjati Perkasa Cilacap - Elda Ainun Ermis; Sudiyono; Nandang Bekti Karnowati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
The company demands its employees to produce good performance. The performance results of each employee will be different because it is influenced by several factors including personality, communication and work stress. For this reason, this study was conducted with the aim of testing and analyzing the influence of personality, communication and work stress towards employee performance at PT. Gunungdjati Perkasa Cilacap. The sample in this study amounted to 58 people with the sampling method used was a census. The data collection technique using questionnaire and the data analysis techniques used are validity and reliability test, classical assumption test, multiple linear regression test, and hypothesis test which using statistical data processing software. The results showed that personality has a significant positive influence towards employee performance, but communication and work stress has no influence towards employee performance. Personality, communication and work stress simultaneously has a significant positive influence towards employee performance. The contribution of the variables of personality, communication and work stress of 0,263 (26,3%) towards the performance of employees at PT. Gunungdjati Perkasa Cilacap.